A comparative Study of Birth Asphyxia and Prematurity (Journal of Dhaka National Medical College & Hospital, 2015)
Introduction: Thousands of physically and mentally handicapped children are posing increasing burden to the society every year as a sequilae of prematurity and birth asphyxia. The problem is multifactorial and we carried out a study for better understanding and management of these babies. Methodology. This prospective comparative study was carried out in the obstetric and neonatal ward of Dhaka National Medical College Hospital during July to September, 2015. 20 preterm neonates without birth asphyxia and 20 full-term birth asphyxiated babies and 20 full-term normal neonates (control group) were include in our study result. Majority of the mothers of both preterm and birth asphyxia babies were primipara 70% & 75% respectively but there was no significant difference between the two groups.Also frequency of maternal illness was more among both preterm and birth asphyxia in comparison to the control group. Prematurity and birth asphyxia was also more frequently associated with multiple pregnancy (10% )& ( 15% ) respectively in comparison to control group 5%.Rupture of membrane was also more in preterm delivery (20%) and birth asphyxia (25%) in comparison to control group (15%). Incidence of caesarean section was also more in both preterm (30%) and birth asphyxia (25%) in comparison to control (20%)J.Dhaka National Med. Coll. Hos. 2015; 21 (02): 35-37